2011
DOI: 10.1364/ome.1.001326
|View full text |Cite
|
Sign up to set email alerts
|

FDTD modeling to enhance the performance of an organic solar cell embedded with gold nanoparticles

Abstract: Optical enhancement is demonstrated in a bilayer P3HT-C-60 solar cell by embedding gold nanoparticles directly into the P3HT layer of the photovoltaic device. FDTD simulations are used to model the observed performance gain. A qualitative agreement between the experimental and numerical results is achieved. This validates the numerical model and the simulation is subsequently extended to predict the performance gain of the bilayer device constructed with thinner P3HT layer. The numerical results reveal that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…4(b). These mode behaviors have previously been explored in the literature [31], [32]. At off-plasmonic-resonance mode at 500 nm, weak field around the nanopillar is shown in Fig.…”
Section: Device Structure Simulation Results and Discussionmentioning
confidence: 74%
“…4(b). These mode behaviors have previously been explored in the literature [31], [32]. At off-plasmonic-resonance mode at 500 nm, weak field around the nanopillar is shown in Fig.…”
Section: Device Structure Simulation Results and Discussionmentioning
confidence: 74%
“…This is consistent with an electron affinity of gold, which for example, causes a charge separation in organic solar cells. 41 The large size of the gold nanoparticles enables many Rh6G molecules to bind, which are then effectively quenched by a short range mechanism, perhaps electron transfer. 54 This sort of fluorescence quenching process is well known for Rh6G on silver nanoparticles, where it plays an important role in enabling single molecule spectroscopy 5 and is likely to play a similar role in gold nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…This negative charging of the nanoparticles is the key reason for long-term stability of the colloidal solution and can be linked to the strong electron affinity to gold that was observed in organic solar cells. 41 Exact mechanism of nanoparticle growth under laser irradiation needs further investigation. Usual growth predicted via microscopic solvability theory can be strongly violated at short time scales; 42 also, a strong ionization 43 of solution due to filamentation and white light continuum generation is expected to favor high zeta potential values required for stability of colloidal solution.…”
Section: Figurementioning
confidence: 99%
“…< /10, where is the particle size, and is the incident wavelength) to create strong light field enhancement in the closest vicinity of the nanoparticle [3][4][5]. Noble metal nanoparticles (NPs) deposited on patterned nanostructures have shown better enhancement of the absorption crosssection in several kinds of solar cells, due to the plasmonic effect, and have given birth to the new concept of plasmonic solar cell [6][7][8][9][10][11]. Recent investigations demonstrated that partially ordered noble metal nanostructures exhibit further surface plasmon electric field enhancement up to several times [12].…”
Section: Introductionmentioning
confidence: 99%